Akibat Hukum Klien Yang Wanprestasi Terhadap Success Fee Kepada Kuasa Hukum Yang Menangani Perkara Ditinjuau Dari Hukum Perdata Dan Undang-Undang Advokat (Studi Kasus Kantor Hukum Kota Bengkulu) - Wandira, Dia Ayu; Jaya, Dwi Putra; Pase, Ana Tasa (JURNAL HUKUM SEHASEN, 2026)
In a success fee agreement, there is a period of time given to the legal counsel, but clients often fail to fully comply with it, resulting in default. This study is an empirical legal study on the Legal Consequences of Client Default on Success Fees to Legal Counsel as viewed from Civil Law and the Advocate Law, with a case study at a law firm in Bengkulu City. Breaches of contract often occur when clients do not pay success fees after winning a case, even though the relationship between clients and advocates is a contract that gives rise to rights and obligations as stipulated in the Civil Code and the Advocate Law. This study aims to determine the legal consequences of client default and the legal measures that can be taken by attorneys. The results of the study show that clients who do not fulfill their payment obligations are considered negligent in accordance with Article 1238 of the Civil Code. Attorneys have the right to issue a summons, and if it is still not fulfilled, they can claim damages based on Article 1243 of the Civil Code. The legal measures commonly taken are warnings, summonses, negotiations, and mediation, as confirmed through interviews with advocates in Bengkulu City. These measures are in accordance with the provisions of Law Number 18 of 2003 concerning Advocates.